Respiratory motion correction of PET using MR-constrained PET-PET registration - Balfour, Daniel R. (Biomed Eng Online, 2015)
BACKGROUND: Respiratory motion in positron emission tomography (PET) is an unavoidable source of error in the measurement of tracer uptake, lesion position and lesion size. The introduction of PET-MR dual modality scanners opens a new avenue for addressing this issue. Motion models offer a way to estimate motion using a reduced number of parameters. This can be beneficial for estimating motion from PET, which can otherwise be difficult due to the high level of noise of the data. METHOD: We propose a novel technique that makes use of a respiratory motion model, formed from initial MR scan data. The motion model is used to constrain PET-PET registrations between a reference PET gate and the gates to be corrected. For evaluation, PET with added FDG-avid lesions was simulated from real, segmented, ultrashort echo time MR data obtained from four volunteers. Respiratory motion was included in the simulations using motion fields derived from real dynamic 3D MR volumes obtained from the same volunteers. RESULTS: Performance was compared to an MR-derived motion model driven method (which requires constant use of the MR scanner) and to unconstrained PET-PET registration of the PET gates. Without motion correction, a median drop in uncorrected lesion [Formula: see text] intensity to [Formula: see text] and an increase in median head-foot lesion width, specified by a minimum bounding box, to [Formula: see text] was observed relative to the corresponding measures in motion-free simulations. The proposed method corrected these values to [Formula: see text] ([Formula: see text] ) and [Formula: see text] ([Formula: see text] ) respectively, with notably improved performance close to the diaphragm and in the liver. Median lesion displacement across all lesions was observed to be [Formula: see text] without motion correction, which was reduced to [Formula: see text] ([Formula: see text] ) with motion correction. DISCUSSION: This paper presents a novel technique for respiratory motion correction of PET data in PET-MR imaging. After an initial 30 second MR scan, the proposed technique does not require use of the MR scanner for motion correction purposes, making it suitable for MR-intensive studies or sequential PET-MR. The accuracy of the proposed technique was similar to both comparative methods, but robustness was improved compared to the PET-PET technique, particularly in regions with higher noise such as the liver.